Trainerprogrammable Logic Controller Dilengkapi Human Machine Interface (HMI) Guna Penguatan Praktek Otomasi Industri - Maun Budiyanto; Y Wahyo Setiyono; Asnal Effendi (Universitas Batanghari Jambi, 2022)
The learning system in vocational education is more directed to practical learning. Therefore, learning media is needed that can make students learn interactively and independently. The research aims to create an industrial automation system learning media as a learning medium for industrial automation courses. The learning media is in the form of a programmable logic controller (PLC) trainer equipped with sensors and combined with a human machine interface (HMI). PLC trainer is made because PLC devices are widely used in industrial automation systems. The PLC component has not been equipped with a display, therefore in this study PLC is combined with HMI. HMI is an interface that connects machines with humans. The Outsel PLC was chosen because the price is very affordable and developed by domestic developers. Trainers are made in a compact form, and easy to carry anywhere. Several simulations were carried out to test the function of the trainer. The test results of the PLC trainer show that the PLC trainer is able to control the process according to the logic programmed, and the HMI is able to display the ongoing process, thereby increasing the interaction between machines and humans.